It’s written in the massive stars: the role of stellar physics in the formation of black holes - Laplace, Eva; Schneider, Fabian; Podsiadlowski, Philipp (Astronomy and astrophysics, 2025)
In the age of gravitational-wave (GW) sources and newly discovered local black holes (BHs) and neutron stars (NSs), understanding the fate of stars is a key question. Not every massive star is expected to successfully explode as a supernova (SN) and leave behind a NS; some stars form BHs. The remnant left after core collapse depends on explosion physics but also on the final core structure, often summarized by the compactness parameter or iron core mass, where high values have been linked to BH formation. Several independent groups have reported similar patterns in these parameters as a function of mass, characterized by a prominent “compactness peak” followed by another peak at higher masses, pointing to a common underlying physical mechanism. Here, we investigate the origin of this pattern by computing detailed single-star models of 17 to 50 solar masses with MESA. We show that the timing and energetics of the last nuclear burning phases determine whether or not stars will reach a high final compactness and iron-core mass and will likely form BHs. The first and second compactness increases originate from core carbon and neon burning, respectively, becoming neutrino dominated, which enhances the core contraction and ultimately increases the iron-core mass and compactness. An early core neon ignition during carbon burning, and an early silicon ignition during oxygen burning, both help counter the core contraction and decrease the final iron core mass and compactness. Shell mergers between C/Ne-burning and O-burning shells further decrease the compactness and we show that these mergers are due to an enhanced entropy production in those layers. We find that the final structure of massive stars is not random but already “written” in their cores at core helium exhaustion, when the core structure is characterized by the central carbon mass fraction XC and the CO core mass. The same mechanisms determine the final structure of any star in this core mass range, including binary products; though binary interactions induce a systematical shift in the range of expected BH formation due to changes in XC. Finally, we discuss the role of uncertainties in stellar physics and how to apply the findings presented here to studies of GW sources.
Online verfügbar: 07. März 2025
Gesehen am 14.08.2025